Ethical and Practical Considerations for Collecting Research-Related Data from Commercially Sexually Exploited Children. Issue 3 (3rd July 2018) - Rothman, Emily F.; Farrell, Amy; Bright, Katherine; Paruk, Jennifer
ABSTRACT: This article presents seven challenges of collecting primary (i.e., firsthand) data from commercially sexually exploited children (CSEC). We drew on our research team's experience collecting longitudinal data from 28 CSEC survivors with a 12-month follow-up period. We used both face-to-face and electronic group brainstorming methods to nominate a list of research-related challenges. The two main themes that were identified were challenges that can limit data quality and concerns about the impact of research on participants, researchers, and others. The three challenges related to data quality are (1) the age of the research participants; (2) questions about obtaining informed consent from parents or guardians; and (3) the over-interrogation of CSEC youth. The four challenges related to concerns about the impact of research were (4) concerns that research participation may further exploit youth; (5) staying in the role of researcher and refraining from providing advocacy; (6) secondary trauma and burnout experienced by research staff; and (7) the additional burden that research and data collection may place on the advocates and direct service providers. Because the process of collecting data from CSEC youth can be complicated, and rife with ethical and practical challenges, we have relayed our experiences with seven specific research-related challenges in order to stimulate discourse and further progress in the field.